(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study investigates the influence of various teacher-related factors on the academic performance of students in slum areas of Jaipur District, Rajasthan, India. Recognizing the unique challenges faced by students in these underprivileged areas, the research focuses on understanding how teacher attributes and behaviors significantly affect student outcomes. Utilizing a sample of 500 students from the slum regions of Jaipur, the study employs survey methodology to gather academic scores and chi-square testing to analyze responses and examine academic achievement. The findings reveal that teacher qualifications, particularly holding a Bachelor of Education degree, and gender are significant predictors of student achievement (Goldstein et. al., 2011 and Nitko, 2001). Conversely, teachers without higher education qualifications are associated with lower academic performance among their students (Sakiz 2015 and Waseka et. al. 2016). The study highlights the critical role of teacher-related factors in shaping educational outcomes and suggests that targeted professional development and improved teacher recruitment policies can enhance academic performance in slum areas.